Retzius-sparing robot-assisted laparoscopic radical prostatectomy: functional and early oncologic results in aggressive and locally advanced prostate cancer - Nyarangi-Dix, Joanne; Görtz, Magdalena; Gradinarov, Georgi; Hofer, Luisa; Schütz, Viktoria; Gasch, Claudia; Radtke, Jan Philipp; Hohenfellner, Markus (BMC urology, 2019)
Retzius-sparing robot-assisted laparoscopic radical prostatectomy (rsRARP) allows entire prostatectomy procedure via the pouch of Douglas. In low- and intermediate-risk prostate cancer (PCa) there is level 1 evidence that the Retzius-sparing approach impacts early continence recovery. Since specific data on aggressive and locally advanced cancer is lacking and avoiding rsRARP is presently suggested, we investigated urinary and sexual recovery, perioperative complications and early oncologic outcomes after rsRARP in this particular cohort.